China-ASEAN Free Trade Area: Implications for Sino-Malaysian Economic Relations - Shuat-Mei Ooi; Eḿile Kok-Kheng Yeoh (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2007)
It is a received opinion that China's emergence as a regional and global power is the most pivotal transformation underway in East Asia. China's enhanced economic standing in Asia has given her new political influence in the region as her trade with the neighbouring states, in particular the member countries of the Association of Southeast Asian Nations (ASEAN) to her south, has been expanding rapidly in recent years. The stunning economic growth of China has created tremendous business opportunities and signed deals has been drawing increasing volume of foreign investment into this Asian giant that was described to have shaken the world - not with her armies, but with her factories. Whether this market is really that huge with potential as has often been presumed and taken for granted is today a topic hotly debated all over the world. With increasing number of foreign companies setting up their businesses in China and the China-ASEAN Free Trade Area - projected to be the world's largest FTA covering 1.7 billion consumers with a combined GDP of USdollar2 trillion and to be completed within ten years from the setting of its framework agreement in November 2002 - poised to become the core of a broader East Asian economic zone in years to come, this paper attempts to explore the implications, opportunities and challenges arising with the establishment of the ACFTA, the achievement, prospect and challenges with respect to the Early Harvest Program (EHP) and Agreement on Trade in Goods (TIG), potential competition arising from the free flow of goods, impacts on growth, production sharing, possible trade diversion effects and institutional and other factors in market penetration, within the context of both global business linkages and domestic market nexus in the light of the expanding China-Malaysian bilateral trade and China's deepening partnership with ASEAN. Keywords: China, ASEAN, Malaysia, CAFTA/ACFTA, trade, investment
hdl:10398/7391
Keywords: 330; malaysia; asean; kina